Effective mechanism for pricing on the product scope of the services - Леонов, Я.; Завацька, Н. (Slobozhanskyi Herald of Science and Sport, 2011)
This paper describes the features of an effective mechanism for pricing on the product scope of the services. Identified factors that influence the pricing policy of the enterprise. Suggested areas of improvement of pricing policy in order to improve the quality of service to consumers.